Central and Eastern Europe : Roads to Growth - Winckler, Georg (International Monetary Fund, 1992)
The experience of Central and Eastern European countries with moving from centrally planned to open-market economies is examined in this collection of papers given at an April 1991 seminar, moderated by Georg Winckler and organized by the IMF and the Austrian National Bank.